Clinical Findings and Electrodiagnostic Testing in Ulnar Neuropathy at the Elbow and Differences According to Site and Type of Nerve Damage. (February 2020) - Vinciguerra, Claudia; Curti, Stefania; Aretini, Alessandro; Sicurelli, Francesco; Greco, Giuseppe; Mattioli, Stefano; Mondelli, Mauro
Abstract : Objective: The aim of the study was to evaluate the clinical and electrodiagnostic testing in ulnar neuropathy at the elbow and differences according to site (humeroulnar arcade vs. retroepicondylar groove) and injury physiopathology (axonal vs. demyelinating), through prospective multicenter case-control study. Design: Cases and controls were matched by age and sex. Ulnar neuropathy at the elbow diagnosis was made on symptoms. Statistical analysis was performed using Mann-Whitney, χ 2, and analysis of variance tests. Results: One hundred forty-four cases and 144 controls were enrolled. Sensory loss in the fifth finger had the highest sensitivity (70.8%) compared with clinical findings. Motor conduction velocity across elbow reached the highest sensitivity (84.7%) in localizing ulnar neuropathy at the elbow recording from at least one of the two hand muscles (first dorsal interosseous and abductor digiti minimi). Abnormal sensory action potential amplitude from the fifth finger occurred more frequently in axonal than in demyelinating forms. Differences between retroepicondylar groove and humeroulnar arcade regarded conduction block and job type. Conclusions: Clinical findings have less usefulness than electrodiagnostic testing in ulnar neuropathy at the elbow diagnosis. Motor conduction velocity across elbow recorded from both abductor digiti minimi and first dorsal interosseous increases diagnostic accuracy. Axonal forms have greater clinical and electrodiagnostic testing severity than demyelinating forms, which are more frequent in retroepicondylar groove. Manual workers prevailed in humeroulnar arcade. These findings may be helpful in prognostic and therapeutic approaches. Abstract : Supplemental digital content is available in the text.